Costs implications of pneumococcal vaccination of adults aged 30–60 with a recent diagnosis of diabetes. Issue 8 (22nd February 2021) - Hutton, David W.; McCullough, Jeffrey S.; Prosser, Lisa; Ye, Wen; Herman, William H.; Zhang, Ping; Pilishvili, Tamara; Pike, Jamison
Highlights: Pneumococcal vaccination rates are low, but rising in non-elderly, commercially-insured individuals. Individuals with diabetes were more likely to be vaccinated. Pneumococcal vaccination has a modest impact reducing costs of pneumococcal disease in this population. Abstract: Objective: The 23-valent pneumococcal polysaccharide vaccine is routinely recommended for adults with diabetes, but little is known about adherence to this recommendation and how vaccination of these adults affects costs related to pneumococcal disease. Research design and methods: We used data from a commercial insurance claims dataset to examine a cohort of non-elderly adults with a new diagnosis of diabetes and adults with no diagnosis of diabetes from 2005 to 2014. We examined rates of pneumococcal polysaccharide vaccination and the relationship between vaccination and pneumococcal disease costs, comparing results for persons with a diagnosis of diabetes and those with no diagnosis of diabetes. Results: Overall rates of pneumococcal polysaccharide vaccination among adults 30–60 years old were <1%/year. Rates of pneumococcal polysaccharide vaccination were higher for adults with diabetes. Pneumococcal polysaccharide vaccination rates more than doubled from 2.9% per year in 2005 to 6.0% per year in 2014 for adults vaccinated during the same year as their diabetes diagnosis. Using a two-part differences-in-differences model on a propensity-score matched dataset, pneumococcal polysaccharide vaccination may reduce average annual per-person pneumococcal disease costs by 90.54 [95% CI: 183.59, -2.49, (p = 0.056)] in persons with diabetes from two years before to two years after vaccination. Conclusions: Non-elderly adults with diabetes have low but rising rates of pneumococcal polysaccharide vaccination. Pneumococcal polysaccharide vaccination has a modest impact reducing overall costs of pneumococcal disease in this population.